Wall Object Design in Maze Game Using Cellular Automata Algorithm - Furqan Malem (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2023)
Games can be an excellent learning tool for kindergarten students considering that children are happy to play at that age. For this reason, this research tries to create a maze-type educational game with the theme "Environmental Cleanliness," which teaches children to clean up garbage and trains them in awareness of the importance of environmental cleanliness. The maze game uses the Cellular Automata Algorithm for designing wall objects so that the difficulty level of the maze can be increased at each level. The maze will change if it meets certain conditions, creating a more exciting and fun educational game for children. This implemented algorithm aims to provide challenges, improve strategy skills, and train directional and spatial awareness by knowing the spaces and paths that must be passed, pointing their location in the maze game. The result of this research is that all features in the game design developed have been successfully implemented and functioned properly. Especially ensuring the algorithm used to generate the maze wall can work according to the design.